Exploring Existence of Host-Guest Inclusion Complex of β-Cyclodextrin of a Biologically Active Compound with the Manifestation of Diverse Interactions - Habibur Rahaman; Niloy Roy; Aditi Roy; Samapika Ray; Mahendra Nath Roy (Emerging Science Journal, 2018)
The host–guest interaction of p-nitro benzaldehyde as guest β-Cyclodextrins have been investigated which have significant applications in the field of medicine such as controlled drug delivery. The 1H NMR study confirms the formation of inclusion complex while surface tension and conductivity studies support the formation inclusion complex with 1:1 stoichiometry. The stoichiometry of the inclusion complex was also supported with Job’s plot method by UV-Visible spectroscopy. FT-IR spectra and SEM study also support the inclusion process. Association constants of  the inclusion complexes have  been  calculated using  the  Benesi–Hildebrand  method,  while  the  thermodynamic  parameters  have  been  estimated  with  the help  of  van’t  Hoff  equation.